Application of “One Syndrome and One Product” nursing model in nursing care of patients with optic atrophy (“一证一品”护理模式在青盲患者中的应用探讨) - LI Xianglu (李享璐); ZHANG Shuai (张帅); WANG Wei (王玮); WANG Qiao (王俏); HUANG Shaolan (黄少兰) (中西医结合护理)
Objective To evaluate the application of “one syndrome and one product” nursing model in nursing care of patients with optic atrophy. Methods Sixty patients diagnosed as optic atrophy (Qingmang) from July 2018 to December 2018 were included into the control group, and 60 patients diagnosed as optic atrophy (Qingmang) from January 2019 to June 2019 were recruited as study group. The control group received routine nursing intervention and the experimental group accepted the nursing pattern based on “one syndrome and one product” nursing model , including integrated nursing ward round, humanistic care based on Traditional Chinese Medicine (TCM) nursing, standardized TCM measures for different syndrome types, TCM nursing path management and quality control. Self-made questionnaire was used to evaluate the Patient satisfaction, and Self-rating Anxiety Scale (SAS) was used to measure the anxiety status of patients. The evaluation of nursing quality was conducted. Results The SAS score of two groups decreased after nursing intervention, and SAS score in the study group was lower than that in the control group (P＜0. 01). The score for the evaluation of nursing quality and satisfaction rate in the study group were higher than those in the control group. Conclusion In the nursing care of patients with optic atrophy, “one syndrome and one product” nursing model is potentially effective to relieve the anxiety status of patients and improve the quality of specialized care. (目的 探讨“一证一品”护理模式在眼科青盲患者中的应用情况。方法 选取2018年7月—12月收治的60例青盲患者作为对照组, 实施常规护理干预; 选取2019年1月—6月收治的60例青盲患者作为研究组, 实施“一证一品”护理干预, 包括医护一体化护理查房, 实施中医护理人文关怀, 针对不同证型形成标准化中医护理措施, 进行中医护理路径管理和质量控制等。采用自制量表调查患者满意度, 采用焦虑自评量表评价(SAS)评估患者焦虑程度, 并开展护理质量评价。结果 干预后2组SAS评分均较干预前下降, 且研究组SAS评分低于对照组, 差异有统计学意义(P＜0. 01)。研究组护理质量评价得分高于对照组, 患者护理满意度高于对照组。结论 在青盲患者的护理中增加“一证一品”护理模式, 能有效改善患者焦虑程度, 对提升患者护理满意度和专科护理质量具有积极意义。)